Business Strategy in the Model of Linear Activity Analysis of Production - Besssenyei, István (International Journal of Engineering and Management Sciences, 2016)
It was analyzed how the methodology of linear activity analysis of production model supports the implementation of different business strategies at a company level. Aspects of analysis are focusing on openness for markets, lean management and environmental protection strategies. The study reveals that the linear activity analysis of production – mainly due to its efficient process optimization problem solving ability – is capable supporting lean management decisions and implementing additional objectives in business strategies. Such objectives can be sustaining specific production patterns for further development or following strategies for limiting market competition. It will be shown how to quantify the costs of strategic objectives in linear activity analyzing model.